Teaching Materials for Environmental Related Courses in Agriculture Occupations Programs - Bohning, Kermit B.; Stitt, Thomas R.; Southern Illinois Univ., Carbondale. Dept. of Agricultural Industries ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
The lesson plans were designed to provide the practicing applied biological and agricultural occupations teacher with a series of units setting down a basic foundation in Environmental Education. Nine lesson plans cover (1) ecosystems and agriculture, (2) biotic communities and food chains, (3) energy and nutrient flow, (4) land use and supply, (5) population distribution and growth, (6) the energy crisis, (7) natural resources, (8) food production and supplies, and (9) current events concerning our ecological system. Each unit provides an introduction, statement of purpose, objective, the presentation, suggested activities, aids, and bibliography. The units are designed for use at the ninth and tenth grade levels. (MS)
ERIC Note: See also CE 000 566 and CE 000 567.
Educational level discussed: Grade 10.
Educational level discussed: Grade 9.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Agricultural Education; Agricultural Occupations; Courses; Curriculum Guides; Ecology; Environment; Environmental Education; Grade 10.; Grade 9.; Instructional Materials; Land Use; Lesson Plans; Pollution; Population Distribution